INVITRO ANTIINFLAMMATORY ACITIVTY OF FLOWER EXTRACT OF COUROUPITA GUINENSIS AUBL - S, SUMATHI; R, ANURADHA (Innovare Journal of Ayurvedic Sciences, 2016)
The nature has provided abundant plant wealth for all the living creatures, which possess medicinal virtues. Hence, the present study aims to open new avenues for the improvement of medicinal uses of Couroupitaguinensis flower for the selected area for invitroanti-inflammatoryactivity was evaluated using human red blood cell membrane stabilization. Diclofenac sodium was used as a standard standarddrug. The percentage of membrane stabilization for CGEF (Couroupitaguinensisethanolic flower) extract, CGMF(Couroupitaguinensismethanolic flower) extract and diclofenac sodium were done at different concentrations. The maximum membrane stabilization of CGMF extract was found to be 70.58Â±7.1 at a dose of 500Âµg/ml compared with CGEF extract and standard drug. Keywords: CGEF extract, CGMF extract, invitro anti inflammatory